Tinjauan Hukum Islam Terhadap Batas Usia Minimal Perkawinan Menurut Undang-Undang Perkawinan - Putri, Izzafi Imellya; Lestari, Ahdiana Yuni (Universitas Muhammadiyah Yogyakarta, 2023)
The minimum age of marriage for a man and woman according to Article 7 paragraph (1) of Law No. 16 of 2019 is 19 years. This paper will discuss how Islamic law reviews the minimum age of marriage according to Law No. 16 of 2019 concerning Marriage. The type of research is normative juridical law research using primary, secondary, and tertiary legal materials. The processing of research materials is carried out by examining the approach of theories, concepts, reviewing the relevant laws and regulations or with a statutory approach. The research material was analyzed in a qualitative descriptive manner. The result of his research is that the minimum age limit for marriage in Law No. 16 of 2019, which is 19 years for men and women, is considered mature to meet the age of maturity in accordance with Islamic religious teachings. However, Islamic law provides for marriage requirements when puberty is complete. Maturity does not depend on age but on the ability and ability to carry out marriage. In addition, the comparative analysis of the minimum age limit for marriage according to Islamic law and Law No. 16 of 2019 concerning Marriage is not much different. Because the Marriage Law is based on the Qur'an, further in Islamic law it is regulated in the Compilation of Islamic Law as a complement to the Marriage Law. Thus, the rules in the Marriage Law are acceptable to the community because there are no provisions that violate Islamic law.